Immunomodulatory Role of the Extracellular Matrix Within the Liver Disease Microenvironment - McQuitty, Claire E.; Williams, Roger; Chokshi, Shilpa; Urbani, Luca (Frontiers in Immunology, 2020)
Chronic liver disease when accompanied by underlying fibrosis, is characterized by an accumulation of extracellular matrix (ECM) proteins and chronic inflammation. Although traditionally considered as a passive and largely architectural structure, the ECM is now being recognized as a source of potent damage-associated molecular pattern (DAMP)s with immune-active peptides and domains. In parallel, the ECM anchors a range of cytokines, chemokines and growth factors, all of which are capable of modulating immune responses. A growing body of evidence shows that ECM proteins themselves are capable of modulating immunity either directly via ligation with immune cell receptors including integrins and TLRs, or indirectly through release of immunoactive molecules such as cytokines which are stored within the ECM structure. Notably, ECM deposition and remodeling during injury and fibrosis can result in release or formation of ECM-DAMPs within the tissue, which can promote local inflammatory immune response and chemotactic immune cell recruitment and inflammation. It is well described that the ECM and immune response are interlinked and mutually participate in driving fibrosis, although their precise interactions in the context of chronic liver disease are poorly understood. This review aims to describe the known pro-/anti-inflammatory and fibrogenic properties of ECM proteins and DAMPs, with particular reference to the immunomodulatory properties of the ECM in the context of chronic liver disease. Finally, we discuss the importance of developing novel biotechnological platforms based on decellularized ECM-scaffolds, which provide opportunities to directly explore liver ECM-immune cell interactions in greater detail.